Kompetensi Pendidik Ideal Berbasis Al-Qur'an (Telaah terhadap Q.S. Luqman; 12, Q.S. Ar-Rahman: 1-5, Q.S. An-Najm: 3-10, Q.S. An-Nahl: 43-44) - Akmal Rizki Gunawan (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Al-Qur'an-Based Ideal Educator Competencies (A study of Q.S. Luqman; 12, Q.S. Ar-Rahman: 1-5, Q.S. An-Najm: 3-10, Q.S. An-Nahl: 43-44)The purpose of this study is to analyze theoretical concepts regarding the competence of ideal educators based on the Quran. In this study, the author used the maudhu'i interpretation method, which served to comprehensively explore the thematic ideas of the